2020
DOI: 10.1007/s42399-020-00504-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Multiple Sclerosis: Predisposition and Precautions in Treatment

Abstract: Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), leading to Coronavirus disease 2019 (COVID-19), is not always confined to the respiratory tract, while patients with can develop neurological manifestations. The patients with multiple sclerosis (MS) pose challenges in this pandemic situation, because of the immunosuppressive medications they get and the fact that viral infections may contribute to MS exacerbation and relapses as an environmental factor in genetically predisposed indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Multiple sclerosis (MS) is a subacute immune-mediated and demyelinating disease of the CNS. The patients' neurological manifestations often exacerbate and relapse due to infection or stress (Sadeghmousavi and Rezaei, 2020 ). The mainstay therapy is immunosuppressants.…”
Section: Neurological Complications Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS) is a subacute immune-mediated and demyelinating disease of the CNS. The patients' neurological manifestations often exacerbate and relapse due to infection or stress (Sadeghmousavi and Rezaei, 2020 ). The mainstay therapy is immunosuppressants.…”
Section: Neurological Complications Of Covid-19mentioning
confidence: 99%
“…The mainstay therapy is immunosuppressants. In such cases, patients may suffer from severe lymphopenia with poor prognosis if they are involved in COVID-19 simultaneously (Dersch et al, 2020 ; Sadeghmousavi and Rezaei, 2020 ). Additionally, they may develop emerging MS due to post-inflammatory immune response.…”
Section: Neurological Complications Of Covid-19mentioning
confidence: 99%
“…However a clear causative correlation between SARS-CoV-2 and the new onset or exacerbation of demyelinating diseases is yet to be determined [72]. It has been speculated that SARS-CoV-2 may activate lymphocytes and induce an inflammatory response leading to exacerbation or new onset of demyelinating disorders [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Use of immunosuppressive therapies in MS patients might cause extra risks in the course of COVID-19. However, published case reports noted that taking DMTs was not related with a significantly enhanced risk of hospitalization or fatal outcome [ 121 ]. Parrotta et al demonstrated that the most common COVID-19 symptoms among MS patients taking DMTs were cough and fever; however, 21% of patients had neurologic symptoms return, which occurred coinciding with the SARS-CoV-2 infection.…”
Section: Does Infection Of Sars-cov-2 May Be An Actual Neurodegenementioning
confidence: 99%